Micro, small and medium enterprise upgrading in India: learning from success cases - Caroline Reeg (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
In low and middle-income countries micro, small and medium enterprises (MSMEs) constitute a large part of the industrial fabric. By offering possibilities to gain income, training and work experience MSMEs are said to provide livelihoods to millions of people worldwide. However, across developed and developing economies empirical observations suggest that most micro and small enterprises are stagnating and only a minority of firms manages to upgrade their businesses into medium and large enterprises. In this study, upgrading is defined as successful firm-level innovation inducing growth in the enterprise's returns, assets or number of regular employees. Different strands of literature suggest five major groups of factors affecting upgrading: (1) entrepreneur characteristics, (2) enterprise characteristics, (3) social and (4) business networks and (5) factors associated with the business environment. This study seeks to understand twofold: (i) which factors affect enterprise upgrading, and (ii) how does the process of enterprise upgrading unfold. To do so, the study adopts a qualitative approach. The core element of this empirical research is a survey with 93 entrepreneurs covering three economic sectors and regions in India. The study finds that while MSME upgrading takes place it is bound to a combination of factors which is highly sector- and region-specific. It further shows that many success factors driving enterprise upgrading are related to the entrepreneur's capabilities and his or her exposure in certain social and business networks. Access to markets and access to finance are severe upgrading constraints, while informality and regulatory burdens are not perceived as being major constraints to upgrading in themselves.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Kleinstunternehmen; KMU; Unternehmenswachstum; Indien